FAKTOR MATERNAL PADA KEJADIAN STUNTING - Farid Fadhlurrahman Fajri (Yayasan Pendidikan Medika Indonesia, 2021)
Stunting is one of the chronic growth disorders associated with height growth based on age which can increase morbidity and mortality, cognitive decline, motor, language development, learning ability, and work capacity. The prevalence of stunting in Indonesia based on the 2018 Riskesdas report shows that it is 30.8 percent or around 7 million children under five. The causes of stunting are multifactorial. Maternal or maternal factors are one of the things that affect stunting. The purpose of this paper is to determine maternal factors in the incidence of stunting. The method used is literature research by searching for the keywords stunting, maternal factor, and maternal factor on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From several studies conducted, maternal or maternal factors related to the incidence of stunting include knowledge of maternal nutrition, maternal height, maternal education level, and mother's occupation.